Broods of five fledglings in the Eurasian eagle-owl (Bubo bubo) - Pérez-García, Juan M.; Sánchez-Zapata, José A.; Botella, Francisco; Donázar, José A.; Hiraldo, Fernando; Sayago, J.M. (Journal of Raptor Research, 2010)
Peer Reviewed